2016
DOI: 10.3791/53949
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Primary Neurogenesis in <em>Xenopus</em> Embryos Using Immunostaining

Abstract: Primary neurogenesis is a dynamic and complex process during embryonic development that sets up the initial layout of the central nervous system. During this process, a portion of neural stem cells undergo differentiation and give rise to the first populations of differentiated primary neurons within the nascent central nervous system. Several vertebrate model organisms have been used to explore the mechanisms of neural cell fate specification, patterning, and differentiation. Among these is the African clawed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The ventricular zone, which, at this stage (NP36) is one to four cells thick, encloses the ventricle of the CNS, and contains neural precursor cells (NPCs) (Noctor et al, 2001; Rakic, 2009; Thuret et al, 2015), which can be identified by expression of Sox3 [SRY (sex determining region Y)-box 3] (Koyano et al, 1997; Macedoni-Luksic et al, 2009; Zhang et al, 2016) (Fig. 7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ventricular zone, which, at this stage (NP36) is one to four cells thick, encloses the ventricle of the CNS, and contains neural precursor cells (NPCs) (Noctor et al, 2001; Rakic, 2009; Thuret et al, 2015), which can be identified by expression of Sox3 [SRY (sex determining region Y)-box 3] (Koyano et al, 1997; Macedoni-Luksic et al, 2009; Zhang et al, 2016) (Fig. 7).…”
Section: Resultsmentioning
confidence: 99%
“…We also examined the localization of MyT1 (Myelin Transcription factor 1), a marker for primary differentiated neurons (Bellefroid et al, 1996; Zhang et al, 2016), which are located more distally to the ventricle and are non-overlapping with the Sox3 positive NPCs (Thuret et al, 2015). In control embryos, neurons are localized outside of the ventricular zone and in particular, seem to be more lateral on the dorsal side (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation